IMPROVEMENT OF TEACHER WORK PRODUCTIVITY THROUGH STRENGTHENING COMMITMENT TO PROFESSIONALISM AND SUPERVISION OF SCHOOL PRINCIPALS USING CORRELATIONAL STATISTICAL ANALYSIS AND SITOREM METHODS - Eka Suhardi; Atep Yulia Nugraha; Soewarto Hardhienata (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
Teacher work productivity can affect the progress of the quality of learning in schools. From the initial survey, it is seen that the work productivity of teachers, especially private junior high school teachers, has not been as expected, meaning "das sein" has not been like "das sollen". Therefore, the teacher's work productivity is interesting to be studied. The research aims to find an effort to increase teacher work productivity by examining the relationship between other variables with teacher work productivity. The other variables are commitment to the profession and supervision of the principal. This research was conducted using the correlational statistical method to find out whether commitment to the profession and supervision of the principal has a positive relationship with teacher work productivity. Based on these results, an analysis was then performed using the Sitorem Method to establish recommendations and find a priority order for improvement of the indicators of the research variables needed. The study was conducted on private junior high school teachers in Klapanunggal District, Bogor Regency with a population of 134 teachers, with a proportional random sample of 100 teachers. The results showed that there was a positive relationship between commitment to the profession with teacher work productivity with a correlation coefficient of 0.512, there was a positive relationship between the supervision of principals with teacher work productivity with a correlation coefficient of 0.464, and there was a positive relationship between commitment to the profession and supervision of principals as together with teacher work productivity with a correlation coefficient of 0.676. This shows that teacher work productivity can be increased through strengthening commitment to the profession and supervision of the principal. The results of Sitorem's analysis show that strengthening commitment to the profession and supervision of school principals can be done by improving indicators that are still weak and maintaining good indicators. Indicators that are still weak and require improvement in the order of priority handling are as follows: 1. Professional development efforts, 2. Services to students, 3. Guidelines for student success, 4. Responsibility, 5. Love of the profession, 6. Provision of feedback from results supervision, 7. follow up supervision, 8. Continuity of supervision, 9. Provision of assistance and guidance, 10. Interaction in supervision, 11. Speed of completing work, 12. Personal development, 13. Positive contribution to the environment, 14. Targets to be achieved , and 15. Relationships with fellow teachers. Whereas the 3 indicators that are in good condition and remain to be maintained are: 1. Obedience to the rules, 2. Quality of work, and 3. Compliance with work